Hubungan antara Psychosocial Safety Climate dengan Depressive Symptoms pada Karyawan PT X - Afifah Nurul Fadilah; Endang Dwiyanti (Lembaga Pengembangan Kinerja Dosen, 2026)
Depressive symptoms in the workplace are an occupational health issue that needs attention. Psychosocial Safety Climate (PSC) is considered one of the key factors that can protect employees’ psychological well-being. This study aims to analyze the relationship between psychosocial safety climate and depressive symptoms among employees of PT X. A quantitative cross-sectional approach was employed, involving total sampling of 30 employees. Psychosocial safety climate was measured using the PSC-12 questionnaire, while depressive symptoms were assessed using the Beck Depression Inventory-II (BDI-II). Data analysis was conducted using the Spearman rank correlation test. The majority of workers were male (53%) and aged between 31–35 years (40%). Most participants were categorized as having mild depression (13 individuals; 43.3%). In terms of psychosocial safety climate, the majority were classified in the high-risk category (15 individuals; 50%). The results of the Spearman correlation test indicated a significant positive relationship between psychosocial safety climate and depressive symptoms (p < 0.001; r = 0.702). This suggests that higher levels of PSC risk are associated with higher levels of depressive symptoms among employees. Therefore, management is recommended to strengthen PSC-related practices and implement workplace-based mental health programs.